Engineering of a highly stable metal-organic Co-film for efficient electrocatalytic water oxidation in acidic media. (September 2020) - Younus, H.A.; Vandichel, M.; Ahmad, N.; Ahlberg, E.; Busch, M.; Verpoort, F.
Abstract: Water oxidation is traditionally performed over IrO2 and RuO2 owing to their high stability at low pH compared to molecular O2 evolution catalysts. The low stability of molecular complexes in acids limits their industrial exploitation as anodes in water-splitting devices, where high current densities and proton conductivity are required. Herein, an existing Co(1, 10-phenanthroline)2 complex film is engineered to improve its pH-stability via extra OH substituents on the ligand, i.e. 1, 10-phenanthroline-4, 7-diol. This novel Co(1, 10-phenanthroline-4, 7-diol)2 complex film is active for water oxidation at low overpotentials and stable at low pH. Since the calculated water oxidation overpotentials of both complexes are similar, the difference in water oxidation activity is attributed to a smaller charge transfer resistance, which originates from a different anchoring style to the electrode via the OH groups of the ligand. This result is supported by electrochemical impedance measurements. The high pH-stability of the Co(1, 10-phenanthroline-4, 7-diol)2 film is computationally rationalized by a high crystal formation energy observed in DFT calculations. In summary, an acid-stable and active cobalt-based metal-organic film is reported that competes well with most reported earth-abundant catalysts for water oxidation under similar conditions. Graphical abstract: Image 1 Highlights: A [Co(1, 10-phenanthroline)2 ] catalyst is engineered to increase the pH-stability and its water oxidation performance. OH groups of Co(1, 10-phenanthroline-4, 7-diol)2 provide electrode anchor points lowering the charge transfer resistance. The catalyst film displayed high activity and excellent stability under high operating potential in acidic conditions. The supreme pH-stability of Co(1, 10-phenanthroline-4, 7-diol)2 could be rationalized by a high film formation energy (DFT).